Medical students' knowledge of HPV, HPV vaccine, and HPV-associated head and neck cancer - Eric Y. Du; Eric Adjei Boakye; Derian B. Taylor; Duaa Kuziez; Rebecca L. Rohde; Jaibir S. Pannu; Matthew C. Simpson; Rolvix H. Patterson; Mark A. Varvares; Nosayaba Osazuwa-Peters (Taylor & Francis Group, 2022)
On the basis of their training, medical students are considered "the best case scenario" among university students in knowledge of the human papillomavirus (HPV). We evaluated differences in knowledge of HPV, HPV vaccine, and head and neck cancer (HNC) among medical students. A previously validated questionnaire was completed by 247 medical students at a Midwestern university. Outcomes of interest were knowledge score for HPV and HPV vaccine, and HNC, derived from combining questionnaire items to form HPV knowledge and HNC scores, and analyzed using multivariate linear regression. Mean scores for HPV knowledge were 19.4 out of 26, and 7.2 out of 12 for HNC knowledge. In the final multivariate linear regression model, sex, race, and year of study were independently associated with HPV and HPV vaccine knowledge. Males had significantly lower HPV vaccine knowledge than females (β = −1.53; 95% CI: −2.53, −0.52), as did nonwhite students (β = −1.05; 95% CI: −2.07, −0.03). There was a gradient in HPV vaccine knowledge based on the year of study, highest among fourth year students (β = 6.75; 95% CI: 5.17, 8.33). Results were similar for factors associated with HNC knowledge, except for sex. HNC knowledge similarly increased based on year of study, highest for fourth year students (β = 2.50; 95% CI: 1.72, 3.29). Among medical students, gaps remain in knowledge of HPV, HPV vaccine, and HPV-linked HNC. Male medical students have significantly lower knowledge of HPV. This highlights the need to increase medical student knowledge of HPV and HPV-linked HNC.